What is context anyway? Reflections on the experience of the Reproductive Health Working Group in the Arab Countries and Turkey - Livia Wick; Hanan Abdul Rahim; Jocelyn DeJong; Weeam Hammoudeh; Aysecan Terzioglu; Yesim Yasin (Reproductive Health)
Abstract Background Contextualizing research involves making connections to the broader environment to understand relationships and relevance. This commentary zooms in on the question of how context matters to knowledge production by reflecting on the experience of the Reproductive Health Working Group in Arab Countries and Turkey (RHWG). Summary In a region such as the Middle East and North Africa that is living through ongoing wars and crises, the network has paid attention to context in multiple ways: as an object of study, as a way to structure the network itself and as a way to conceptualize research support. From its very beginning in 1988, RHWG focused on the importance of social context to understand reproductive health issues. With time, the network became a capacity-building body supporting researchers working on gender and health in situations in which the context itself (the field or the site of empirical data collection) was being destroyed by crises and wars. Furthermore, context structures network activities, in particular the research workshop. The research workshop brings together scholars from the region in a supportive space to share their work thereby reducing isolation caused by wars and crises. In addition, context is an organizing principle and object of study in and of itself at the workshops. Discussions and interpretations of the research papers involve contextualizing them, that is making connections to relations in its surroundings. Conclusion We have learned over the years that contextualizing research projects is not simply about putting together a historical and social story alongside the work on reproductive health. Contextualizing means thinking about what the concept of context does. In addition, we have learned that to do contextualized research we need to overcome the isolation of researchers created by wars and borders.